RELATIONSHIP OF PATTERN OF FOOD FOR NUTRITION WITH NUTRITIONAL STATUS ON TOLLS AGED 6 – 24 MONTHS IN THE AREA OF INTEGRATED SERVICES IN MELATI VILLAGE, KARANGAGUNG PALANG - mustainah, amirotun; sumiatin, titik; Al Busthomy, Aby Yazid (Global Ten Public Health and Nursing Journal, 2023)
The prevalence of malnutrition in Indonesia continues to increase. On a broad scale, malnutrition can be a threat to the resilience and survival of a country. Around 16% or 101 million children under the age of five suffer from malnutrition. Based on 2018 Basic Health Research data, in Indonesia, there are 17.7% of children under the age of 5 years experiencing nutritional problems. One of the factors is inappropriate complementary feeding (MPASI). The purpose of this study is to determine the relationship between complementary feeding patterns and nutritional status in toddlers aged 6 – 24 months in the Posyandu Melati, Karangagung Palang Village. The research design of this study is an observational analytic study, which is an analysis of the relationship between 2 or more variables and is determined based on statistical tests. The design used in this study is correlational using a cross-sectional approach which aims to determine the relationship between variables where the independent and dependent variables are identified in one unit of time with a population of 56 mothers under five and use a total sample. The Chi-Square test obtained a significant value of 0.001 (sing <0.05). It showed that there was a relationship between the pattern of complementary feeding and the nutritional status of children aged 6-24 months in the Posyandu Melati, Karangagung Village, Palang District, with the Spearman rank correlation test, the result is 0.545 which means the strength of the relationship is moderate. Complementary foods must be given at the proper frequency, amount, and age.The pattern of regular complementary feeding will affect the good nutritional status of toddlers. To maintain a decent nutritional status, regular complementary feeding patterns must be implemented.